2010
DOI: 10.1002/hed.21650
|View full text |Cite
|
Sign up to set email alerts
|

Association of p16INK4a overexpression with improved outcomes in young patients with squamous cell cancers of the oral tongue

Abstract: Background. The aim of this study was to examine biomolecular profiles in a cohort of young adults with squamous cell cancers (SCCs) of the oral tongue.Methods. We identified all patients aged 18 to 39 years diagnosed with SCC of the oral tongue at our institution. Immunohistochemical (IHC) staining was performed for p16 INK4a , epidermal growth factor receptor (EGFR), phosphorylated-EGFR (pEGFR), p53, and ERCC1. Human papillomavirus (HPV) testing was performed using in situ hybridization (ISH) and polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
106
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 25 publications
7
106
2
3
Order By: Relevance
“…Genetic factors have also been studied vastly as a risk factor for developing HNSCC in young adults and as a prognosis determinant; while polymorphisms of DNA repair genes have not been established to be responsible for developing the disease in young adults Kostrzewska et al, 2012), over-expression of p16(INK4a) has been found to be associated with favorable prognosis in young patients with SCCs of the oral tongue (Harris et al, 2011) and Pfeiffer et al have found regions of DNA deletions (named germline loss of heterozygosity) that may contribute to genetic susceptibility for HNSCC in young adults and non-smokers (Pfeiffer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors have also been studied vastly as a risk factor for developing HNSCC in young adults and as a prognosis determinant; while polymorphisms of DNA repair genes have not been established to be responsible for developing the disease in young adults Kostrzewska et al, 2012), over-expression of p16(INK4a) has been found to be associated with favorable prognosis in young patients with SCCs of the oral tongue (Harris et al, 2011) and Pfeiffer et al have found regions of DNA deletions (named germline loss of heterozygosity) that may contribute to genetic susceptibility for HNSCC in young adults and non-smokers (Pfeiffer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that head and neck squamous cell carcinoma human papillomavirus-positive and p16 expressing is different from classic head and neck squamous cell carcinoma, but it is not clear whether head and neck squamous cell carcinoma human papillomavirus-positive and p16 non expressing (probably, tobacco/alcohol-related tumors that are infected by high-risk human papillomavirus) represents a group biologically distinct from human papillomavirus-negative tumors (Cheng et al, 1995). Other studies in (Smith et al, 2012;Harris et al, 2011) have confirmed better disease-specific and recurrence-free survival in human papillomavirus and/or p16 positive tumors.…”
Section: P16 Expressingmentioning
confidence: 99%
“…Given that the rate of p53 mutation is quite low in human papillomavirus-associated tumors, the addition of p53 mutation sequencing could have added valuable information had sufficient tissue been available (Harris et al, 2011). There have been conflicting data on p53 expression in human papillomavirus positive head and neck squamous cell carcinoma tumor cells.…”
Section: P16 Expressingmentioning
confidence: 99%
See 2 more Smart Citations